Sobre elementos em grupos finitos cujos índices de seus centralizadores são potências de primo - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Acre, 2014)
In the present work we are interested in ﬁnding suﬃcient conditions for elementx∈G to have prime-power index. Letx an be element in a groupG, we will denote byIndG(x) the index ofCG(x) inG. More generally, ifH≤G we denote the index [H :CH(x)] by IndH(x).
Keywords: Grupos finitos - índice centralizador; Potência de número primo; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA